Civil Liability of the Bank Regarding Safe Deposit Boxes: A Case Study of the Robbery at the National Bank Dānishgāh Branch - Jafar Zanganeh Shahraki; Seyed Mostafa Milani (آموزه‌‌های فقه مدني)
The provision of safe deposit boxes is one of the services that banks offer to their customers. The bank’s civil liability for any damage to customers’ assets stored in these safes, along with the extent of this liability, has gained significant attention following the robbery incident at the Melli Bank safe deposit box facility on May 24, 2022, in Tehran. This liability can be examined from various perspectives. Firstly, Article 35 of the Banking and Monetary Law of the Country generally holds banks liable for damages arising from banking operations. Secondly, the legal nature of these funds (deposits) is a subject of dispute, and the acceptance of any viewpoint affects the extent of liability. Thirdly, the condition of non-liability (Article 7 of the National Bank’s Leasing Funds Regulations) is the basis on which the contract has been signed by the customers. This article employs a descriptive-analytical approach to assess Bank Melli’s responsibility towards the victims of the robbery incident. The findings reveal that Bank Melli bears legal responsibility for this event, and the non-liability clause outlined in the Fund’s bylaws (regulation or provision) cannot be invoked due to the bank’s gross failure.